Highly acidic pH facilitates enamel protein self-assembly, apatite crystal growth and enamel protein interactions in the early enamel matrix - Zhang, Youbin; Jin, Tianquan; Zhu, Weiying; Pandya, Mirali; Gopinathan, Gokul; Allen, Michael; Reed, David; Keiderling, Timothy; Liao, Xiubei; Diekwisch, Thomas G. H. (Frontiers in Physiology, 2022)
Tooth enamel develops within a pH sensitive amelogenin-rich protein matrix. The purpose of the present study is to shed light on the intimate relationship between enamel matrix pH, enamel protein self-assembly, and enamel crystal growth during early amelogenesis. Universal indicator dye staining revealed highly acidic pH values (pH 3-4) at the exocytosis site of secretory ameloblasts. In studies mimicking the gradual increase of pH in an amelogenin solution transitioning from pH 3 to 7, there was (i) a coiled configuration identified by electron capture dissociation at low pH that resolved with increasing pH, and (ii) a dramatic change in Fourier transform infrared spectra above pH 7. When increasing the pH of an amelogenin solution from pH 5 to pH 7, there was a gradual increase in subunit compartment size from 2nm diameter subunits at pH 5 to a stretched configuration at pH6 and to 20nm subunits at pH 7. HSQC NMR spectra revealed that the formation of the insoluble amelogenin self-assembly structure at pH 6 was critically mediated by at least 7 of the 11 histidine residues of the amelogenin coil domain (AA 46-117). Comparing calcium crystal growth on polystyrene plates, crystal length was more than 20-fold elevated at pH 4 when compared to crystals grown at pH 6 or pH 7. To illustrate the effect of pH on enamel protein self-assembly at the site of initial enamel formation, molar teeth were immersed in phosphate buffer at pH4 and pH7, resulting in the formation of intricate berry tree-like assemblies surrounding initial enamel crystal assemblies at pH4 that were not evident at pH 7 nor in citrate buffer. Amelogenin and ameloblastin enamel proteins interacted at the secretory ameloblast pole and in the initial enamel layer, and co-immunoprecipitation studies revealed that this amelogenin/ameloblastin interaction preferentially takes place at pH 4 – pH 4.5. Together, these studies highlight the highly acidic pH of the very early enamel matrix as an essential contributing factor for enamel protein structure and self-assembly, apatite crystal growth, and enamel protein interactions.